Helping academics escape the publishing trap: an introduction to copyright literacy - Morrison, Chris; Secker, Jane (My University, 2018)
Presentation at RepoFringe 2018 - Helping academics escape the Publishing Trap: am introduction to copyright literacy by Dr Jane Secker, City University and Chris Morrison, University of Kent
Keywords: copyright literacy; publishing